Curriculum Development Management of Islamic Education in The Internet of Things Era - Pahrudin, Agus; Wakidi, Wakidi; Anggini, Viggy (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2023)
To effectively address the changing global landscape of the 21st century, Islamic education must undergo a significant overhaul, particularly in the area of curriculum management. This article provides a comprehensive evaluation of the strategies employed in the administration of the Islamic education curriculum in the present day. This research employs a methodology that involves analyzing literacy and doing a thorough assessment of existing books. Through a comprehensive examination of the structure and fundamental principles, we investigate the significance of curriculum management in addressing the requirements of Islamic education in contemporary times. The integration of multiple perspectives is achieved through the utilization of an interdisciplinary approach. The research findings indicate that there is a pressing necessity to enhance the administration of Islamic education curriculum in the 21st century. The primary obstacles addressed encompass the incorporation of contemporary technologies, enhancing digital proficiency, and modifying curricular content to accurately represent worldwide circumstances. The noteworthy discoveries pertain to the necessity of adopting new methods in education that prioritize creativity, critical thinking, and cultural literacy. In order to ensure the pertinence of Islamic education to contemporary needs, curriculum management must take into account these factors. Furthermore, the research findings emphasize the necessity of adopting an interdisciplinary methodology in the creation of educational programs, facilitating the fusion of religious knowledge, science, technology, and the humanities. This can produce graduates that possess not just expertise in religious matters, but also have the capability to make valuable contributions towards resolving intricate issues in the contemporary global community. In summary, a thorough evaluation of the progress made in managing the curriculum of Islamic education in the 21st century highlights the necessity for innovation, adjustment, and preparedness to confront the ever-changing landscape of education and society.